Sustainability and Energy Potential of Extrusion Processed Biomass Briquettes: A Systematic Literature Review - Bimo Aji, Dody; janan, Ahmad Janan Febrianto; , Reza Bayu Kurniawan; , Gahar Albani Rasyid; , Iqbal Maulana (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The global energy crisis and the increasing volume of agro-industrial waste have accelerated the development of environmentally friendly and sustainable biomass-based alternative energy sources. Extrusion technology has emerged as a promising approach for converting biomass waste into high-quality energy briquettes with enhanced thermal performance and minimal environmental impact. This study aims to analyze the energy potential and sustainability contributions of extrusion-based biomass briquettes through a Systematic Literature Review (SLR) approach, providing a multidimensional thematic understanding of recent research trends. The review follows the PRISMA protocol and utilizes the Scopus database, systematically selecting 30 scientific articles published between 2019 and 2025 based on predefined inclusion and exclusion criteria. The analysis focuses on feedstock characteristics, processing technologies, energy outputs, and contributions to environmental, economic, and social sustainability. The findings reveal that agro-industrial residues such as rice husks, straw, and food waste, when processed through extrusion with natural binders, produce briquettes with high calorific values, low emissions, and efficient combustion performance. This approach also promotes waste reduction, cost efficiency, and the empowerment of community-based renewable energy enterprises. The study concludes that extrusion technology holds strategic potential in supporting the transition toward renewable energy and achieving sustainable development goals, applicable to both industrial and household energy scales.